2017
DOI: 10.14207/ejsd.2017.v6n3p423
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Role of Biofertilization on Yield Related Characteristics of Two Apple Cultivars and Soil Microorganisms Under Orchard Conditions

Abstract: Intensive development of agriculture and increasing utilization of synthetic nitrogen fertilizers significantly contributes to a series of undesirable effects and results in excessive environmental pollution. Approximately half of all nitrogen applied to boost agricultural production escapes its intended use and is lost to the environment. Over the past years, fruit growing practice has been focused on a new concept, which relies primarily on the application of microbial inoculants i.e. biofertilizers. In line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Inoculation with Azotobacter, Pseudomonas, and Bacillus cultures increased yield of apple cvs. 'Granny Smith' and 'Čadel' as compared to artificial fertilization [21]. Biofertilizer application (based on Bacillus, Pseudomonas, Lysobacter and Ohtaekwangia species) increased the yield as well as microbiological and biochemical activity of the soil in the long-term study in China [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inoculation with Azotobacter, Pseudomonas, and Bacillus cultures increased yield of apple cvs. 'Granny Smith' and 'Čadel' as compared to artificial fertilization [21]. Biofertilizer application (based on Bacillus, Pseudomonas, Lysobacter and Ohtaekwangia species) increased the yield as well as microbiological and biochemical activity of the soil in the long-term study in China [21].…”
Section: Introductionmentioning
confidence: 99%
“…'Granny Smith' and 'Čadel' as compared to artificial fertilization [21]. Biofertilizer application (based on Bacillus, Pseudomonas, Lysobacter and Ohtaekwangia species) increased the yield as well as microbiological and biochemical activity of the soil in the long-term study in China [21]. Monoculture inoculation of chernozem soil with A. chroococcum and B. mucilaginosus enhanced the soil microbial activity and optimized its available nutrient content, but the yield was significantly lower than in the orchard fertilized by chemical fertilizers at a maximal studied rate (broad applied N120P60K120 and fertigated with N35P25K35) [23].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, research has been intensified to limit the use of mineral fertilizers (due to environmental costs) and to improve the fertility of arable soils through the use of various types of biofertilizers (Mosa et al 2016;Pešaković et al 2017;Zhu et al 2020). Derkowska et al (2014;2017) observed that the use of Micosat F, a preparation containing microorganisms, had a positive effect on the root system of apple trees.…”
mentioning
confidence: 99%